Perception of running shoe cushioning: wear test vs. controlled experiment - Pisciotta, Eric; Shorten, Martyn (Footwear science, 2018)
Footwear developers employ feedback from human wear testers to assess the functionality and acceptability of their products. However, there is often poor correspondence between perceptions reported in wear tests and in vitro measurements of running shoe characteristics. This study evaluated runners' ability to perceive differences in running shoe cushioning under controlled conditions and compared those results with wear test outcomes. Five running shoe conditions were chosen based on the ASTM F1976 impact test results (g-max) to span a typical range of cushioning scores with g-max differences among shoes distributed between 0.9 and 6.5 g. Samples of each shoe condition were used by an independent group of wear testers for about one month and 160 km of running. They provided ratings of various shoe attributes, including 'heel cushioning' and 'forefoot cushioning', using a 1-7 Likert-type scale. In a laboratory study, 50 healthy runners evaluated the same five shoe conditions and ranked them from 'least cushioned' to 'most cushioned'. For each of the 10 possible pair-wise shoe comparisons, the probability that subjects would rank the shoes consistently with g -max scores was calculated as a function of the difference in g-max between shoes. There were no significant differences in wear test cushioning ratings among the four most cushioned shoes. However, using the ranking protocol, subjects were able to detect differences in cushioning with a 'least noticeable difference' of 1.4 g and demonstrated increasing sensitivity with larger difference magnitudes. In contrast to a typical wear test protocol, the laboratory test demonstrated that runners are able to perceive cushioning differences of sufficient magnitude, consistent with mechanical test results, under appropriately controlled conditions.